Choline Metabolism Alteration: A Focus on Ovarian Cancer - Bagnoli, Marina; Granata, Anna; Nicoletti, Roberta; Krishnamachary, Balaji; Bhujwalla, Zaver M.; Canese, Rossella; Podo, Franca; Canevari, Silvana; Iorio, Egidio; Mezzanzanica, Delia (Frontiers in Oncology, 2016)
Compared to normal differentiated cells, cancer cells require a metabolic reprogramming to support their high proliferation rates and survival. Aberrant choline metabolism is a fairly new metabolic hallmark reflecting the complex reciprocal interactions between oncogenic signaling and cellular metabolism. Alterations of the involved metabolic network may be sustained by changes in activity of several choline transporters as well as of enzymes like choline kinase-alpha (ChoK-α) and phosphatidylcholine-specific phospholipases C and D. Of note, the net outcome of these enzymatic alterations is an increase of phosphocholine and total choline-containing compounds, a “cholinic phenotype” that can be monitored in cancer by magnetic resonance spectroscopy. This review will highlight the molecular basis for targeting this pathway in epithelial ovarian carcinoma (EOC), a highly heterogeneous and lethal malignancy characterized by late diagnosis, frequent relapse and development of chemoresistance. Modulation of ChoK-α expression impairs only EOC but not normal ovarian cells, thus supporting the hypothesis that "cholinic phenotype" is a peculiar feature of transformed cells, and indicating ChoK-α targeting as a novel approach to improve efficacy of standard EOC chemotherapeutic treatments.